2015
DOI: 10.7603/s40930-015-0002-x
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in Higher Education: An Exploratory Investigation of Hospitality Management Courses

Abstract: This paper aims to investigate students' perceptions about sustainability curricula in hospitality management degree programmes. Sustainability, a prime business concern, is now a prominent agenda in higher education, and also in hotel management courses. The study is located in India and adopts a positivist epistemological position. Quantitative data was collected through structured questionnaires from 250 undergraduate students undergoing hospitality degree programmes in the states of Jammu and Kashmir. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Various pieces of evidence have been found to support this notion. Anderson (2017) found a strong correlation between taking related university courses and attitude towards engaging in environmentally sustainable behaviour and activities, while sustainability-related modules have deeply impacted students' attitudes towards the sustainability agenda (Chawla & Manhas, 2015). Nevertheless, studies have yet to discover the attitudinal outcome pertaining to sustainability as the result of enrolling in online and distance education programmes (Oliveira et al, 2018;Silas Marques de Oliveira, 2012).…”
Section: Attitude Towards Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Various pieces of evidence have been found to support this notion. Anderson (2017) found a strong correlation between taking related university courses and attitude towards engaging in environmentally sustainable behaviour and activities, while sustainability-related modules have deeply impacted students' attitudes towards the sustainability agenda (Chawla & Manhas, 2015). Nevertheless, studies have yet to discover the attitudinal outcome pertaining to sustainability as the result of enrolling in online and distance education programmes (Oliveira et al, 2018;Silas Marques de Oliveira, 2012).…”
Section: Attitude Towards Sustainabilitymentioning
confidence: 99%
“…Meanwhile, students in Irish higher education institutions possess inadequate knowledge and a narrow understanding of sustainable development and know extraordinarily little about social issues (Nicolaou & Conlon, 2012). According to Chawla and Manhas (2015), most students found that the term 'sustainability' is rather unclear, although they were somehow engaged in sustainability-related matters. The findings exemplify a lack of understanding of the complexity of the sustainability agenda, which is largely associated with environmental issues.…”
Section: Sustainability Competencies Acquiredmentioning
confidence: 99%
See 1 more Smart Citation
“…However, accounting educators are still seen to be focusing on the teaching and learning activities to finish the accounting syllabus towards the needs of the examinations rather than inculcating the right accounting ethics and maintaining integrity in the workplace (Ahmad, 2007). Chawla and Nanhas (2015) stated that university accounting students need a single course in ethics to deal with various situations and improve their ethical reasoning skills. Accounting educators viewed the incidents of corporate scandal in the accounting world as a wake-up call to realize the need to incorporate good values to the students and the importance of accounting to society and the economy (Titard et al, 2004;.…”
Section: Introductionmentioning
confidence: 99%